2009
DOI: 10.2106/jbjs.h.00539
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Anterior Cruciate Ligament Reconstruction

Abstract: The rate of anterior cruciate ligament reconstruction has increased in frequency. Also, while anterior cruciate ligament reconstruction appears to be a safe procedure, the risk of a subsequent operation on either knee is increased among younger patients and those treated by a lower-volume surgeon or at a lower-volume hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
194
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(210 citation statements)
references
References 29 publications
8
194
0
3
Order By: Relevance
“…This could suggest that we are underestimating wound complication rates, or simply that patients are presenting other complications that our analysis is unable to capture. Lyman et al [1] also found that low volume units had significantly higher readmission rates. We found no such association with any of the complications investigated in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This could suggest that we are underestimating wound complication rates, or simply that patients are presenting other complications that our analysis is unable to capture. Lyman et al [1] also found that low volume units had significantly higher readmission rates. We found no such association with any of the complications investigated in this study.…”
Section: Discussionmentioning
confidence: 95%
“…This can range from superficial surgical site infection and minor wound complications to septic arthritis of the knee with devastating consequences. Lyman et al [1] looked at complications post surgery and quoted a readmission rate within 90 days of 2.3%. Our 30-day readmission rate was 1.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Несмотря на то, что артроскопическая пластика ПКС является одной из самых распространен-ных ортопедических операций [6], на сегодняш-ний день нет единых критериев оценки состоя-ния трансплантата. По литературным данным, частота неправильной установки трансплантата при пластике ПКС составляет 37,3%, что приво-дит к неудовлетворительным результатам опе-рации у 27,8% пациентов [7]. Успешная рекон-струкция ПКС требует понимания нескольких факторов: анатомического размещения транс-плантата, механических свойств выбранного трансплантата, а также биологических процес-сов, происходящих во время перестройки транс-плантата.…”
Section: Introductionunclassified
“…More recently, a 15-year prospective study in men's professional football by Hagglund and colleagues (2016) showed that 85 % of players returned to training and 65 % of players returned to competitive play within three years following ACLR. Rehabilitation and return to sport outcome measures are widely discussed in the literature (Bradley, Klimkiewicz, Rytel, & Powell, 2002;Lyman et al, 2009) and a number of outcome measures are used in rehabilitation programs to determine the time course for when athletes can return to sport (Bauer, Feeley, Wawrzyniak, Pinkowsky, & Gallo, 2014;Myer, Paterno, Ford, Quatman, & Hewett, 2006;Webster et al, 2017). For many years, isokinetic dynamometry has been considered the gold standard measure of the strength and dynamic stability of the knee joint and is frequently used for the evaluation of the success of the rehabilitation program (Cvjetkovic et al, 2015).…”
Section: Rehabilitation and Return To Sportmentioning
confidence: 99%